2016
DOI: 10.1016/j.trsl.2016.03.016
|View full text |Cite
|
Sign up to set email alerts
|

New models of hematogenous ovarian cancer metastasis demonstrate preferential spread to the ovary and a requirement for the ovary for abdominal dissemination

Abstract: Emerging evidence suggest that many high grade serous ‘ovarian’ cancers (HGSOC) start in the fallopian tube. Cancer cells are then recruited to the ovary and then spread diffusely through the abdomen. The mechanism of ovarian cancer spread was thought to be largely due to direct shedding of tumor cells into the peritoneal cavity with vascular spread being of limited importance. Recent work challenges this dogma, suggesting hematogenous spread of ovarian cancer may play a larger role in ovarian cancer cell meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 36 publications
3
78
0
Order By: Relevance
“…However, the mechanism(s) by which ovulation increases the risk of ovarian cancer is less clear. This is important because recent evidence indicates that colonization of the ovary by FTE-derived tumors may be an important step in the progression of HGSOC [10,13] and suggests that this step may represent a therapeutic target in women at high risk of developing HGSOC [10]. The ovary produces a large number of hormones and growth factors that may stimulate migration of tumorigenic FTE cells to the ovaries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanism(s) by which ovulation increases the risk of ovarian cancer is less clear. This is important because recent evidence indicates that colonization of the ovary by FTE-derived tumors may be an important step in the progression of HGSOC [10,13] and suggests that this step may represent a therapeutic target in women at high risk of developing HGSOC [10]. The ovary produces a large number of hormones and growth factors that may stimulate migration of tumorigenic FTE cells to the ovaries.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Coffman et al found that when injected intravenously, HGSOC cells, but not breast cancer or lung adenocarcinoma cells, colonized the ovary [13]. The lifetime number of ovulations is positively associated with the risk of developing ovarian cancer [14].…”
Section: Introductionmentioning
confidence: 99%
“…Hematogenous metastasis has also been described [7], [8]. Free-floating EOC aggregates are abundant in the peritoneal cavity; however, the number, size, and integrity of aggregates vary considerably [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…Lan Coffman, MD, PhD, revealed vascular spread of ovarian cancers with 3 different metastatic models. 35 They used (1) mouse tail vein injection of ovarian cancer cells, (2) subcutaneous mouse ovarian tumor, and (3) human xenograft ovarian tumor with humanized microenvironment model to demonstrate formation of distant metastases by vascular spread. They observed high rate of metastasis to the ovary in all 3 models, with intra-abdominal metastatic disease and ascites.…”
Section: Mouse Models Of Ovarian Cancermentioning
confidence: 99%